2019
DOI: 10.3390/plants9010029
|View full text |Cite
|
Sign up to set email alerts
|

Rapid High-Yield Transient Expression of Swine Hepatitis E ORF2 Capsid Proteins in Nicotiana benthamiana Plants and Production of Chimeric Hepatitis E Virus-Like Particles Bearing the M2e Influenza Epitope

Abstract: The Hepatitis E virus (HEV) is a causative agent of acute hepatitis, mainly transmitted by the fecal-oral route or zoonotic. Open reading frame (ORF) 2 encodes the viral capsid protein, which is essential for virion assembly, host interaction, and inducing neutralizing antibodies. In this study, we investigated whether full-length and N- and C-terminally modified versions of the capsid protein transiently expressed in N. benthamiana plants could assemble into highly-immunogenic, virus-like particles (VLPs). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…The nucleotide sequences of the whole HEV genotype 3 nucleoprotein (HEV ORF2 1–660) [ 25 ] codon-optimized for N. benthamiana were used as templates for PCR amplification of HEV ORF2 551–607 to construct the pEAQ-HT:HBcHEV ORF2 551–607 ( Figure 2 ). Primers were designed to incorporate SalI and AseI restriction sites and long flexible linkers ((GGS)4) at 5’ and 3’ ends of the HEV ORF2 551–607 region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleotide sequences of the whole HEV genotype 3 nucleoprotein (HEV ORF2 1–660) [ 25 ] codon-optimized for N. benthamiana were used as templates for PCR amplification of HEV ORF2 551–607 to construct the pEAQ-HT:HBcHEV ORF2 551–607 ( Figure 2 ). Primers were designed to incorporate SalI and AseI restriction sites and long flexible linkers ((GGS)4) at 5’ and 3’ ends of the HEV ORF2 551–607 region.…”
Section: Resultsmentioning
confidence: 99%
“…Amplification of DNA fragment for the production of the HEV ORF2 501–607, was carried out by PCR. The target HEV ORF2 551–607 sequences were amplified using the synthetic master gene HEV ORF2 1–660 [ 25 ]. The PCR fragment was flanked by Sal I and Ase I restriction sites (New England Biolabs, Ipswich, MA, USA), which were used for sub-cloning of the PCR fragment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for the production of HEV immunogenic proteins, which can be used for development of serological tests for detection of the HEV infection. In our previous study, we described a method for the production of recombinant HEV open reading frame (ORF) 2 protein in Nicotiana benthamiana plants and the successful use of this protein for serological detection of anti-HEV antibodies in both humans and swine [33,56]. Other studies have also demonstrated the efficacy of rORF2 gt 3 produced in various expression systems in the detection of anti-HEV serum Ab [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The truncated protein was purified in high amounts of up to 100 mg/kg FWT, and could be used as a diagnostic antigen [95]. Attempts were also made to produce HEV VLPs and chimeric M2-HEV VLPs using varying lengths of ORF2 [129]. The immunogenicity and VLP assembly properties of the transiently expressed ORF2 in plants remain to be determined.…”
Section: Expression Of Orf2 As Vlps In Plantsmentioning
confidence: 99%